Effectiveness of interpretive education program in influencing rural secondary school students' conservation behavior - Lim, Evelyn Ai Lin (2014)
Many out-of-school environmental education programs for school students in Malaysia lacked the capacity to influence behavior. The study compares the effectiveness of the non-interpretive and interpretive education programs in influencing rural secondary school students’ intention to be an organizer of a Malayan Tapir education program in school. The study utilized focus group discussion to elicit secondary school students’ attitudes and emotions toward the Malayan Tapir. Students’ salient beliefs toward their involvement as an organizer of a Malayan Tapir education program in school were also elicited based on the Theory of Planned Behavior (TPB) theoretical framework. Findings from the discussion were used to develop a self-reported questionnaire and an interpretive education program based on the enjoy, relevant, organized and thematic (EROT) interpretive model. The pre-test post-test experiment design was utilized to compare the effectiveness of the non-interpretive and interpretive education programs. Pre-test was conducted before the intervention while the post-test was conducted after the intervention. A delayed post-test was conducted six months after the intervention. Data was statistically analyzed to compare the effectiveness of the interventions between groups and tests. Comparing between tests, the pre-test and post-test results for the control group showed no improvement in the TPB constructs mean scores with significant differences observed for the attitude, subjective norm and perceived behavioral control constructs. Non-interpretive group showed no improvement in the TPB constructs mean scores and significant difference was only observed for the subjective norm construct. For the interpretive group, tests mean scores improved for all TPB constructs with significant differences observed for the subjective norm and behavior intention constructs. When the pre-test and delayed post-test were compared to determine the long-term effect of the intervention programs, no significant differences between the mean scores were observed for the control and non-interpretive groups. There were no improvement in the constructs’ mean scores for the interpretive group but significant differences between tests were observed for the attitude and perceived behavioral control constructs. Comparing the four TPB constructs between interventions groups, significant difference in the pre-test was observed for the attitude construct with interpretive group having stronger positive attitude as compared to the control and non-interpretive groups. Significant differences were observed for all TPB constructs in the post-test with interpretive group scoring higher mean scores as compared to the control and noninterpretive groups. No significant differences between groups for all the TPB constructs in the delayed post-test. The conduct of the pre-test had an effect on the groups’ post-test while students’ gender had an effect on the groups’ post-test results. The EROT interpretive results showed that interpretive program was more successful in making the program enjoyable, relevant, organized and thematic; and evoking students’ emotion to take action as compared to the non-interpretive program. The study has shown that the interpretative model was more successful in influencing students’ beliefs toward the Malayan Tapir and students’ intention to be involved as an organizer of the Malayan Tapir education program in school. The interpretive program was also replicable to other locations and wildlife (i.e. Orang utan).